Analisis Beban Kerja Dan Jumlah Tenaga Kerja Pada Bagian Bahan Baku Menggunakan Metode Workload Analysis - Candrianto Candrianto; Radna Ningsih; Alpon Satrianto; Rizki Fadhillah Lubis (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2020)
This research was conducted at PT. XYZ in the garden section, a company engaged in the forestry sector of industrial plants and products that produce HVS paper (such as paper one, otc), paperboard, kiky books, tissue (teas). PT.XYZ manages raw materials that are not in accordance with the target, the purpose of this study is to determine the amount of workload and the number of workers in the garden section at PT. XYZ. To collect the data needed in this study, data collection techniques were used through direct observation of the object under study, interviews and various other reference sources. Data analysis using the Workload Analysis method. From the results of calculations using the method, workload is one aspect that must be considered by every company, and workload must be considered for a worker to get harmony and high work productivity. By using the Workload Analysis method and to find out how much the optimal number of workers is in the raw material section. After analyzing the data using this analysis, it can be obtained that the average workload on the raw material section is 184.39%, which means that the workload is excessive. In order for the workload of each workforce in the garden to be optimal, it is advisable to increase the workload with an average workload of 92.19% so that effectiveness can be achieved.